Proto-Indo-European long vowels and Balto-Slavic accentuation - Pronk, Tijmen (Baltistica, 2012)
The article is a critical review of the evidence regarding the reflexes of Proto-Indo-European long vowels in Baltic and Slavic. It is argued that in Balto-Slavic, inherited long vowels receive circumflex intonation in all positions in the word.  Examples like Lith. várna ‘raven’, žvėrìs ‘wild animal’ and grė́bti ‘to rake’ that are traditionally thought to show that an Indo-European long vowel obtained acute intonation must be explained differently. A number of verbal roots forming a yod-present can be shown to have undergone metatony rude in Lithuanian and Latvian and metatony douce in Lithuanian. There is no evidence for the thesis that Balto-Slavic monosyllables always had circumflex intonation. Lithuanian examples that would show this development can be shown to be due to inner-Lithuanian innovations. Finally, Balto-Slavic ā-stems and intensive verbs with long vocalism generally have circumflex intonation and can be shown to reflect Proto-Indo-European formations containing a long vowel.